1997
DOI: 10.1046/j.1472-765x.1997.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the biosynthesis of fumonisins B1, B2 and B3 by different strains of Fusarium moniliforme

Abstract: The relationship between fungal growth and the production of fumonisin on maize grain by 25 strains of Fusarium moniliforme of different origins has been investigated. Although sporulation was essentially the same for all the strains (about 108 propagules g−1 dry matter), ergosterol assays revealed marked variations in fungal biomass. All strains studied produced highly variable amounts of fumonisin B1, the highest levels being observed in strains of ergosterol content above 400 μg g−1. However, no correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
2
11
1
Order By: Relevance
“…Differences between three temperatures around the optimum (25°C, 30°C and 35°C) were consistent over 18 fungal strains from different geographic origins showing varying sporulation capabilities. Range and amount of sporulation found by Melcion et al (1997) in different strains were similar to those from this study.…”
Section: Discussionsupporting
confidence: 88%
“…Differences between three temperatures around the optimum (25°C, 30°C and 35°C) were consistent over 18 fungal strains from different geographic origins showing varying sporulation capabilities. Range and amount of sporulation found by Melcion et al (1997) in different strains were similar to those from this study.…”
Section: Discussionsupporting
confidence: 88%
“…Although previous studies reported 25°C ± 2°C to be optimal temperatures for fumonisin production (Alberts et al 1990;Melcion et al 1997), this study showed that fumonisin production was higher at 16°C than at 26°C (Figure 1). However, the fumonisin production per unit in this study was not even a fraction of the amount reported by previous studies, where fumonisin production on maize measured >14,000 mg/L and 850 mg/L, after 7 and 10 days respectively (Alberts et al 1990;Melcion et al 1997). In contrast, Garcia et al (2012) reported less than 0.02 mg/L fumonisin after F. verticillioides was incubated on sterile soybeans for 21 days at different temperatures ranging between 15°C and 30°C.…”
Section: Discussioncontrasting
confidence: 64%
“…Mycotoxin production is species-and straindependent, and is influenced by the growth substrate and environmental conditions (D'Mello and Macdonald 1997;Melcion et al 1997;Brzonkalik et al 2011;Garcia et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Water activity (a w ) and temperature influence fumonisin biosynthesis when F. moniliforme is grown in culture on mature maize kernels (3,(14)(15)(16). It has been reported that when the fungus is grown on mature maize grain adjusted to a a w of 1.0 at 25°C, good growth and rapid production of fumonisin B 1 occur (16). Based on desorption isotherms, the a w of intact maize kernels does not begin to significantly decrease until the kernel moisture content falls below approximately 24% (a w , ϳ1.0) (9).…”
mentioning
confidence: 99%